Service Quality of Centre for Social Entrepreneurship Rapid Incubator at Durban University of Technology - Manduth Ramchander; Solomon Nyamurima (Economics and Entrepreneurship: The Proceedings of the 10\(^th\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
Business incubators have emerged as crucial mechanisms for promoting entrepreneurship and boosting global economic growth. These programmes provide aspiring entrepreneurs with essential resources, mentoring, and support services to make it easier to create and launch successful businesses. Consequently, business incubators have become essential components of government agencies, particularly those with a primary focus on entrepreneurship. The study aimed to assess the quality of service provided by the Durban University of Technology Centre for Social Entrepreneurship Rapid Incubator (DUT CSERI). The SERVQUAL questionnaire was used to assess the expectations and perceptions of SMMEs in relation to five quality dimensions. Non-probability sampling and convenience sampling were used to select 330 SMMEs affiliated with the DUT CSERI. Inferential and descriptive statistical analyses were used to evaluate the quality provided by the DUT CSERI. This study revealed that the DUT CSERI offers SMMEs an exceptional quality of service. This is evidenced by the fact that SMME perceptions of service quality exceeded their expectations. However, there is room for continued improvement, as five of the twenty-two service quality gaps were successfully identified. It is recommended that DUT CSERI improve its tangibility and reliability service quality dimensions.